Case Report: Desmoid tumor response to magnetic resonance-guided high intensity focused ultrasound over 4 years - Yeo, Sin Yuin; Bratke, Grischa; Knöll, Peter; Walter, Sebastian Gottfried; Maintz, David; Grüll, Holger (Frontiers in Oncology, 2023)
Desmoid tumors show local aggressive behavior with the tendency of recurrence after resection. The latter is the standard of care especially once the tumor impairs function or invades crucial structures. Other treatment options comprise radiation therapy, nonsteroidal anti-inflammatory drugs (NSAID), chemotherapy, or local thermoablative therapy such as cryotherapy, radiofrequency, microwave ablation, or thermal ablation with high intensity focused ultrasound (HIFU). This report presents a case where a desmoid tumor at the left dorsal humerus was 2 times surgically resected and, after recurrence, thermally ablated with HIFU under magnetic resonance image-guidance (MR-HIFU). In our report, we analyze tumor volume and/or pain score during standard of care (2 years) and after HIFU treatment over a 4-year follow-up period. Results showed MR-HIFU treatment led to complete tumor remission and pain response.